The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/nu9030259
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Diet for the Maintenance of Remission in Inflammatory Bowel Disease

Abstract: Diet has been speculated to be a factor in the pathogenesis of inflammatory bowel disease and may be an important factor in managing disease symptoms. Patients manipulate their diet in attempt to control symptoms, often leading to the adoption of inappropriately restrictive diets, which places them at risk for nutritional complications. Health professionals struggle to provide evidence-based nutrition guidance to patients due to an overall lack of uniformity or clarity amongst research studies. Well-designed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 127 publications
5
74
0
5
Order By: Relevance
“…Families stated a preference for nutritional support as dietary advice instead of MEN. Young people and parents reported an increased interest in their diet after diagnosis, similar to previous findings . Engaging young people with CD in the co‐design of studies on healthy diet and lifestyle choices may positively impact clinical and nutritional outcomes in adulthood and as a patient‐led practice may improve quality of life .…”
Section: Discussionsupporting
confidence: 81%
“…Families stated a preference for nutritional support as dietary advice instead of MEN. Young people and parents reported an increased interest in their diet after diagnosis, similar to previous findings . Engaging young people with CD in the co‐design of studies on healthy diet and lifestyle choices may positively impact clinical and nutritional outcomes in adulthood and as a patient‐led practice may improve quality of life .…”
Section: Discussionsupporting
confidence: 81%
“…Our results indicate that diet is a critical factor affecting development of IL-23-driven experimental IBD, and suggest that it does so by modifying the microbiota. Dietary constituents have been shown to affect the immune response and the inflammatory status, in part by modulating the microbiota 22,50 Our studies showed a marked reduction in alpha diversity as function of the diet change.…”
Section: Discussionmentioning
confidence: 68%
“…Mice bearing specific gene alterations develop colitis, but a significant number of them do not develop colitis when raised in germ-free conditions, suggesting a critical role for genes and the microbiota in promoting disease 4,20 . Other animal studies suggest a critical role of dietary components in the onset and severity of colitis [21][22][23] . Yet, the development of relapsingremitting disease models has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…23) Haskey et al showed that a high protein intake, especially from animal protein, resulted in a 3.3 time increased risk of IBD, suggesting that a diet high in animal protein was a major risk factor. 23) With respect to the intake of dietary fats, a high n3 polyunsaturated fatty acid (PUFA) to n6 PUFA ratio is reportedly inversely associated with the risk of IBD. 2325) Several studies have shown the influence of certain components contained in food on epithelial cell permeability.…”
Section: Diet and Microbiotamentioning
confidence: 99%